Bahasa Inggris - Afrizal Firman; Gwyneth Rachel Sentosa; Angelina Jocelyn Djunaidy; Liong Kellen; Mustika Kusuma Basir (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This research analyzes the influence of Live Streamers and Influencers on Impulsive Buying behavior among Ciputra School of Business (CSB) Makassar students. Using a quantitative approach, the primary data was collected through an online survey using the Google Form tool which had 100 active students as respondents. This research focuses on how Live Streamers and Influencers can affect Impulsive Buying; with data analysis used in the research is Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show a significant positive relationship between Influencer and Impulsive Buying. However, in contrast to previous studies, Live Streamers showed a negative relationship to Impulsive Buying. This indicates that respondents prioritize a product’s value compared to the characteristics of the Live Streamer broadcasting the stream. These findings provide new insight into the impact of digital marketing strategies on student consumer behavior. Furthermore, the findings also provide guidance for businesspeople to design more effective strategies to promote their products.